Sosialisasi Pengembangan UMKM melalui Peningkatan Identitas Usaha dan Daya Saing serta Penyelenggaraan Bazar di Kelurahan Alun-alun Contong: Pengabdian - Dian Febiyanti; Afifah Kamilia Tsabita; Natasya Sabila Najwah; Pramudya Shalahhudin Syach; Leily Suci Rahmatin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an integral part of the national economy. However, many MSMEs still do not fully understand the importance of corporate identity in enhancing corporate branding and product competitiveness. This article describes a community service initiative in the form of outreach and a bazaar held in Alun-alun Contong Village, Bubutan District, Surabaya. The purpose of this outreach was to increase MSMEs' knowledge of branding, digital marketing tactics, and business law. This market provided a platform for MSMEs to gain practical experience and promote their products to the public. The results of the activity demonstrate how education and practice can increase MSMEs' awareness and ability to create unique brands for their businesses, expand customer networks, and strengthen their position in the community economy.